Cross border cooperation in socio-economic Malaysia-Indonesia (Sosek Malindo) cooperation activities to regional development - Hartani, Nira Hariyatie (2013)
Regional policies and development suggest that regions have been increasingly affected by material and non material flows on global scale.Likewise to regional development in West Kalimantan, Indonesia region, it has been performing the development of region on global scale, by developing that prioritizes the development of border regions that has strategic value because has border regions directly on with neighboring country is Sarawak, Malaysia, by building cooperative relationships with the neighboring regions across interstate boundaries.The form of the cooperative relationship is the development of Cross Border Cooperation (CBC) like Sosek Malindo cooperation that is a strategy Tor accelerate the growth of regional development in the context of globalization.Therefore, this study attempt to discover activities of socio-economic Malaysia-Indonesia (Sosek Malindo) cooperation that conducts the activities based on one of CBC's rational foundation, is the economic foundations to regional developments in West Kalimantan region.